Community education as a correlate of participation in community development activities in Ikwuano local government area of Abia state, Nigeria (2020)
The study examined Community education as a correlate of participation in community development activities in Ikwuano LGA in Abia State, Nigeria. Descriptive survey research design was adopted for the study, while two research questions and two hypotheses were generated from the research objectives. The target population of the study comprised 2,238 members of community drawn from 10 communities. Proportionate sampling technique was adopted to select 30% (696) respondents and the Instrument used for data collection was a questionnaire titled: Community Education Correlates of Participation in Community Activities scale (CECOPCDAS). The reliability index of the Instrument was 0.82 determined through the use of Pearson Product moment Correlation Statistics (PPMC). The hypotheses were tested using Pearson Product Moment Correlation (PPMC) analysis at 0.05 level of significance. The findings from the study revealed that community education affected people's participation in community development activities in their communities (Mean = 2.7). It was also found that community education is a social engineering tool for Citizen participation in community development activities in Ikwuano LGA (Mean = 2.5). It was further revealed that there was a significant relationship between community education and Citizen participation in community development activities and levels of awareness on community development activities (r=0.695, p<0.05). In addition, it was discovered that there was significant relationship between community education and the level of citizens' participation in community development activities (r = 0.510, p<0.05). The study therefore recommended among others that community education should be improved and given adequate attention to enhance sustainable development in Nigerian communities